Korelasi Kelimpahan Megabentos dengan Persentase Tutupan Terumbu Karang di Perairan Amed, Kabupaten Karangasem, Bali - Nurdyputra, I Gusti Ngurah Galih Ksatria Mahadhika; Putra, I Nyoman Giri; Atmaja, Putu Satya Pratama (Bumi Lestari, 2024)
The existence of each megabenthos is related to the condition of coral reefs which act as habitats for various types of megabenthos species. Benthos are commonly takes advantage of the ecosytem of coral reef as a habitat to live and shelter in the coral niches from natural predators. This study aimed to determined the abundance of megabenthos and the percentage of coral reef cover, as well as the correlation between the abundance of megabenthos and the percentage of live coral cover in Amed Waters. Megabenthos data collection was carried out using the Benthos Belt Transect (BBT) method. Point Intercept Transect (PIT) was used to examined the coral percentage cover. Correlation of Pearson was used to analyzed the correlation between abundance of megabenthos and coral percentage cover. A total of 473 individuals with a total abundance of 0.26 ind/m2 were found in this study. Interestingly, there were no Acanthaster planci individuals found during the data collection.  The condition of coral reefs was dominated by Dead Coral Algae (DCA), while the percentage value of live coral cover in Amed Waters were 19% to 35% in the damaged to moderate category, respectively. Pearson correlation showed a value of (r) 0.067 with a very weak positive category which indicates that there is a positive relationship between the two variables which indicating that the correlation of megabenthos abundance has no significant relationship with the percentage of live coral cover. Keywords: megabenthos ; Amed ; Pearson ; dead coral algae